Investigation of surface interactions between volatile chromium species and ceramics. (22nd January 2019) - Tatar, Greg; Gannon, Paul; Swain, Nolan; Mason, Ryan; Remington, Emily; Dansereau, Spencer
Abstract : Stainless steels are often used in high temperature (≥500°C) applications such as solid oxide fuel cells (SOFCs), combustion engine exhaust systems, and in power/chemical plant process equipment. At high temperature and in oxidizing conditions, chromium containing oxides, such as chromia, may form protective surface layers on the underlying alloy. Reactive evaporation of chromium, however, may occur from the protective surface layers given these conditions, resulting in the formation of volatile chromium species such as CrO2 (OH)2 . These volatile chromium species may then interact with surrounding materials, potentially resulting in hazardous compound formation, or having detrimental effects on system performance, as in the case of SOFCs. To better understand the interaction of volatile chromium condensation/deposition on material substrates, volatile chromium species were generated from chromia powder at 500°C to 900°C and flowed past coupons of alumina and mica and quartz wool at temperatures ranging from 150°C to 900°C for 24‐ and 100‐hour exposures. The ceramic surfaces were characterized as a function of these exposures using X‐ray photoelectron spectroscopy (XPS). Analysis of Cr 2p3/2 peak positions revealed the influence of temperature, material, and exposure time on the oxidation states of surface chromium compounds and extent of chromium deposition. Potential mechanisms are proposed to help explain the observed trends.